Antibacterial Activity of Nutmeg Oil - Nurjanah, Sarifah; Putri, Indira Lanti; Sugiarti, Dwi Pretti (KnE Life Sciences, 2017)
Indonesia is one of the largest producer of nutmeg oil (Myristica fragrans). This essential oil has a lot of usefulness for food and pharmaceutical industries, however antibacterial activity of Indonesian nutmeg oil has not been investigated yet. Antibacterial activity Myristica fragrans oil from two areas respectively (Sulawesi and Central Java) were investigated. The essential oils was extracted using water and steam distiller and then its antibacterial activity against pathogenic bacteria (gram-positive bacteria : Staphylococcus aureus, Staphylococcus epidermis, and gram-negative bacteria : Shigella Dysenteriae, Salmonella Typhi) was examined. Resistance pattern was studied by in vitro disc diffusion method using essential oil concentration 20%, 40%, 60%, 80% and 100%. The result showed that the two essential oils inhibited all bacteria. The highest inhibition zone on Central Java nutmeg oil was on 60% concentration of the oil (12.96 16.79, 13.46 and 16.50 mm for S. aureus, S. epidermis, S. dysenteriae, S. typhi respectively), while on Sulawesi nutmeg oil was on 100% concentration (18.84, 16.54, 17.84 and 12.54 mm for S. aureus, S. epidermis, S. dysenteriae, S. typhi respectively). Keywords: Antibacterial activity; Nutmeg oil; Central Java; Sulawesi